'Well let me put it uhm the other way around maybe': Managing students' trouble displays in the CLIL classroom. Issue 1 (2nd January 2019) - Aldrup, Marit
ABSTRACT: This study is concerned with repair practices that a teacher and students employ to restore intersubjectivity when faced with interactional problems in a Content and Language Integrated Learning (CLIL) classroom. Adopting a conversation analytic (CA) approach, it examines the interactional treatment of students' verbal and embodied trouble displays in a video-recorded, teacher-fronted geography lesson held in English at a German high school. At the same time, it explores to what extent the repair practices employed are fitted to this specific interactional context. The analysis shows that students' verbal trouble displays often result in extensive repair sequences, whereas students' embodied trouble displays are usually met with teacher self-repair in the transition space. In this way, the latter are resolved much earlier and more quickly. The study further reveals practices like reformulation and translation to be especially useful for repairing interactional problems in classrooms in which a foreign language is used as the medium of instruction. The findings may be of interest for prospective as well as practicing teachers in that they provide relevant insights into how interactional trouble can be successfully managed in (CLIL) classroom interaction.